Diagnostic Value of Imaging Combined With Tumor Markers in Early Detection of Lung Cancer - Wei, Su-Ju; Wang, Li-Ping; Wang, Jun-Yan; Ma, Jing-Xu; Chuan, Feng-Bin; Zhang, Yu-Dong (Frontiers in Surgery, 2021)
Objective: The objective of this research is to explore the diagnostic value of imaging plus tumor markers in the early detection of lung cancer. Methods: Sixty patients with lung cancer treated in our hospital from January 2018 to January 2019 were selected as group A. They were matched with 60 patients with benign lung disease as group B and 60 healthy subjects examined in our hospital as group C. The carcino-embryonic antigen (CEA), CYFRA21-1, and neuron-specific enolase (NSE) were assessed, and the diagnostic value of tumor markers plus imaging in lung cancer diagnosis was explored. Results: The CEA, CYFRA21-1, and NSE in group A were evidently superior to those in groups B and C, and those in group B were superior to those in group C (all P < 0.001). CEA had the highest sensitivity (56.7%), and NSE had the highest specificity (93.3%). The tumor markers plus imaging had the highest sensitivity for different types of lung cancer, and the sensitivity to early lung cancer (90%) was superior to other diagnostic methods (P < 0.05). Conclusion: The tumor markers plus imaging is of great significance in early lung cancer diagnosis and provides a reference for judging the pathological classification.